Increasing blood pressure variability predicts poor functional outcome following acute stroke - Appiah, KO; Nath, M; Manning, L; Davison, WJ; Mazzucco, S; Li, L; John, FP; Rothwell, PM; Panerai, RB; Haunton, VJ; Robinson, TG (Elsevier, 2020)
Introduction Increasing blood pressure variability has been reported following acute stroke, but there is uncertainty about how best to measure it and about the impact on prognosis following acute ischaemic stroke and transient ischaemic attack.